Wind Blasts in Underground Coal Mines: A Study of the Effect of the Rock Mass Properties of the Falling Roof Using a Physical Model - Torabi S. R; Daly C. R (The Australasian Institute of Mining and Metallurgy, 1995)
Wind blast is the sudden movement of air displaced by the massive collapse of roof rock in underground openings and is experienced as a high velocity flow of air through adjacent workings. The initial flow in the outbye direction is often followed by 'suck back', that is a reverse flow of air towards the newly created void. As part of the Wind Blast Project, undertaken by The University of New South Wales, Department of Mining Engineering, a physical model was constructed. One of the functions of the laboratory wind blast model is to provide insight into the dynamics of the interaction between the falling strata and the air being compressed below. During a collapse, some air is expelled into the surrounding roadways while the remainder penetrates towards the top of the roof elements. In this paper two aspects of the rock mass properties which influence the phenomenon are considered: - Flow paths through the falling roof element, ie the permeability of the roof element; - Bed separation prior to the fall which introduces a void above the roof element. A series of tests was carried out utilising the physical model in order to investigate the relationships between the flow of air through the simulated roadways, the variations in gauge pressure above and below the falling roof element, and the acceleration and terminal velocity of the latter, all as a function of the flow paths through the roof element and of the extent of the void above. The results of comprehensive tests using the wind blast physical model suggested that the time history of outbye air flow in the simulated roadway comprises two distinct phases. a) A primary phase, characterised by a high velocity flow of air which exhibits a peak and corresponds to the period during which the roof element is accelerating. The peak air velocity is related to the acceleration of the roof element. b) A secondary phase, characterised by a residual air flow of a lesser velocity than in the primary phase and corresponding to the period during which the roof element is falling at its terminal velocity. The velocity of the residual air flow is directly proportional to the terminal velocity of the roof element. In a monolithic collapse of a roof element it was shown that the presence of flow paths in the roof element increased the air velocity in the roadway in both the primary and the secondary phases. The presence of an air-filled void above the roof element, on the other hand, influenced the air velocity only in the primary phase by increasing the peak air velocity. The overall duration of the process was however decreased as a result. 'plug type' collapses, where roof failure extends to the ground surface, potentially generate the highest peak air velocities likely to be encountered during wind blasts.